Compósitos de acrilonitrila-butadieno-estireno (ABS) reciclado reforçados com tecidos de fibras vegetais e tecidos de fibras de carbono reciclados - Hosokawa, Meire Noriko (2024)
Over the years, increasing technological advances have raised concerns about the quantity and proper management of waste generated in different industry sectors. Polymers such as acrylonitrile-butadiene-styrene (ABS) and carbon fibers are materials widely used in various electronics, automotive, and aeronautics sectors. These materials can also be recycled and reused in the manufacture of new products, promoting the circular economy. Natural fibers, such as jute fibers, belong to a class of materials used as an alternative to replace synthetic fibers and can be combined with recycled polymers such as ABS. In this context, this work aimed to develop hybrid composites using recycled ABS as the matrix and fabrics containing plant fibers and recycled carbon fiber fabrics as the dispersed reinforcing phase. Firstly, a study was carried out on the tensile properties of three types of bidirectional natural fiber fabrics: a jute fiber fabric (single weave, 365 g.cm-2) (T1), a jute fiber fabric (double weave, 445 g.cm-2) (T2) and a jute and cotton fiber fabric (single weave, 360 g.cm-2) (T3). To obtain the recycled carbon fiber fabrics, prepregs containing polymerized epoxy resin were used, which were subjected to heat treatments at different temperatures (450°C, 500°C and 600°C) to establish the best condition to degrade the epoxy resin and recover fabrics with properties suitable for use. The composites were molded using the hot compression method. They were evaluated by mechanical tests (tensile, flexural, and impact), thermogravimetry, water absorption, Fourier transform infrared absorption spectroscopy and scanning electron microscopy. The results showed that T2 and T3 fabrics presented higher tensile strength values and when used as reinforcement in composites, promoted an increase of 21% in tensile strength, 78% in modulus of elasticity, and 19% in flexural strength compared to recycled ABS. Regarding carbon fiber fabrics, the best condition for their recovery was treatment at 500°C for 2 hours, obtaining fibers free of epoxy resin and without apparent degradation. When used as a reinforcement phase, carbon fiber fabrics promoted an increase of 13% in flexural strength and 20% in tensile strength of the composites compared to recycled ABS. Hybridization promoted an increase of up to 16% in flexural strength, 6% in tensile strength, and 43% in impact strength of hybrid composites compared to recycled ABS. Therefore, reusing this type of prepreg containing carbon fibers from industrial waste is a viable alternative to recover high-value materials and reinsert them into the production chain, developing more sustainable products.